VD_FINDINFO Décision / 2014 / 557 vom 15. Januar 2014 - VD Tribunal cantonal (2014)
TÉMOIN, TÉMOIN À CHARGE, APPRÉCIATION DES PREUVES, LÉSION CORPORELLE | 123 CP, 177 CP, 34 CP, 42 CP, 44 CP, 47 CP, 49 al. 1 CP